2011
DOI: 10.1111/j.1365-2214.2011.01294.x
|View full text |Cite
|
Sign up to set email alerts
|

Parents as transition experts? Qualitative findings from a pilot parent‐led peer support group

Abstract: Parents reported gaining new knowledge and became more active and future-oriented in their planning. Further, they strongly valued the facilitator role and benefited from the social support provided by the group. Findings provide a unique snapshot of parental needs. Individualized support with an emphasis on citizenship, participation and inclusion were targeted topics. Future work should continue to explore optimal mechanisms for the provision of parent-focused transition support and the inclusion of parents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
114
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(119 citation statements)
references
References 41 publications
5
114
0
Order By: Relevance
“…The findings support those of previous studies highlighting the importance of shared experience, (Ainbinder et al 1998, Bull 2003, Kerr and McIntosh 2000, Kingsnorth et al 2011, Law et al 2001, Lo 2010, Nicholas and Keilty 2007, Rearick et al 2011, Solomon et al 2001) and learning through the experience and support of others (Ainbinder et al 1998, Bull 2003, Kerr and McIntosh 2000, Kingsnorth et al 2011, Law et al 2001, Rearick et al 2011). These themes reflect the informational, affirmational and emotional support described elsewhere (Sullivan-Bolyai et al 2010, Sullivan-Bolyai and Lee 2011, Ireys et al 1996.…”
Section: Expanding Social Networksupporting
confidence: 82%
See 1 more Smart Citation
“…The findings support those of previous studies highlighting the importance of shared experience, (Ainbinder et al 1998, Bull 2003, Kerr and McIntosh 2000, Kingsnorth et al 2011, Law et al 2001, Lo 2010, Nicholas and Keilty 2007, Rearick et al 2011, Solomon et al 2001) and learning through the experience and support of others (Ainbinder et al 1998, Bull 2003, Kerr and McIntosh 2000, Kingsnorth et al 2011, Law et al 2001, Rearick et al 2011). These themes reflect the informational, affirmational and emotional support described elsewhere (Sullivan-Bolyai et al 2010, Sullivan-Bolyai and Lee 2011, Ireys et al 1996.…”
Section: Expanding Social Networksupporting
confidence: 82%
“…Previous qualitative research in this population has also reported outcomes relating to emotional and personal growth for parents receiving support (Ainbinder et al 1998, King et al 2000, Kingsnorth et al 2011, Rearick et al 2011, Solomon et al 2001). For parents who support others, the satisfaction gained from helping other people (Ainbinder et al 1998, Kerr and McIntosh 2000, Lo 2010, Sullivan-Bolyai and Lee 2011 and the desire to give something back (Solomon et al 2001, Nicholas and Keilty 2007, Law et al 2001, Jenkinson et al 2013) has been highlighted and is consistent with research in other populations on the benefits derived from offering support to others, known as the helper-therapy principle (Solomon 2004, Salzer andShear 2002).…”
Section: Expanding Social Networkmentioning
confidence: 99%
“…Consistent with evidence generated in lengthier qualitative interviews with caregivers who participated in MyTime groups (Hammarberg et al, 2014), most caregivers who responded to the online survey reported significant benefit from participation, including social support from people in similar situations, access to relevant information and ideas and having ''time out''. These themes are congruent with the stated aims of MyTime, and with existing evidence about benefits of peer support for parents and other caregivers of children with special needs (Ainbinder et al, 1998;Bull, 2003;Kerr & McIntosh, 2000;Kingsnorth et al, 2011;Law et al, 2001;Lo, 2010;Nicholas & Keilty, 2007;Solomon et al, 2001). Negative experiences of participation mentioned by respondents to the online survey were also similar to the barriers to participation which emerged from the interviews (Hammarberg et al, 2014), including diversity in group members' socio-economic position and in severity of their children's disabilities.…”
Section: Discussionsupporting
confidence: 73%
“…Only five pertained to peer support groups. These studies (Bull, 2003;Kingsnorth, Gall, Beayni, & Rigby, 2011;Law et al, 2001;Lo, 2010;Solomon et al, 2001) all used qualitative interview or focus group discussion methods. They concluded that parents who attend such groups may experience increased empowerment and sense of social inclusion (Law et al, 2001) and share and learn practical information, including about new treatments, sources of support and services (Papageorgiou & Kalyva, 2010).…”
Section: Current Evidence Regarding Peer Support Groups For Parents Amentioning
confidence: 99%
“…Intervention studies remain limited. One paper reporting the development and evaluation of a peer support group for parents of young people with health conditions transitioning to adulthood [63] found that parents who attended the group gained new knowledge and became more future-oriented and active in their transition preparations. Further research is required to explore the effectiveness of interventions helping parents and young people define and respond appropriately to their shifting roles and responsibilities [8].…”
Section: Discussionmentioning
confidence: 99%